Multimorbidity in Atherosclerotic Cardiovascular Disease and Its Associations With Adverse Cardiovascular Events and Healthcare Costs: A Real-World Evidence Study - Dingwei Dai; Joaquim Fernandes; Xiaowu Sun; Laura Lupton; Vaughn W. Payne; Alexandra Berk (Journal of Health Economics and Outcomes Research)
**Background:** Atherosclerotic cardiovascular disease (ASCVD) remains the leading cause of mortality and disability in the United States and worldwide.